Search This Blog

Wednesday, November 14, 2012

Total energy of earth in its circular orbit around the sun

Question :
Find out the total energy of earth in its circular orbit around the sun in terms of gravitational constant
Let R be the total distance between the earth and the sun. If \({M_e}\) and \({M_s}\) are the mass of earth and sun respectively, the gravitational force of motion of earth and sun is given by
\(F =  - \frac{{G{M_e}{M_s}}}{{{R^2}}}\)
where G is the gravitational constant. Since the centripetal force balances the gravitational force of attraction, we have
\({F_c} = |{F_G}|\),
\({F_c} = \frac{{{M_e}{v^2}}}{R}\)
v being the velocity with which earth is moving. Hence we have
\(\frac{{{M_e}{v^2}}}{R} = \frac{{G{M_e}{M_s}}}{{{R^2}}}\)
\({M_e}{v^2} = \frac{{G{M_e}{M_s}}}{R}\)

Therefore kinetic energy of earth in motion is
\(T = \frac{1}{2}{M_e}{v^2} = \frac{1}{2}\frac{{G{M_e}{M_s}}}{R}\)

As we know that , force in terms of potential energy is
\({F_G} = - \frac{{\partial V}}{{\partial R}}\)
\(V = - \int {{F_G}dR} = \int {\frac{{G{M_e}{M_s}}}{{{R^2}}}dR = - } \frac{{G{M_e}{M_s}}}{R}\)
Now total energy of the earth in the orbit around the sun is
\(E = T + V\)
\(E = \frac{1}{2}\frac{{G{M_e}{M_s}}}{R} - \frac{{G{M_e}{M_s}}}{R}\)

\(E = - \frac{1}{2}\frac{{G{M_e}{M_s}}}{R}\)
This is the required expression.

Thursday, November 8, 2012

Brachistochrone Problem

If a particle falls from rest under the influence of gravity from higher to lower point in the minimum time, what is the curve that the particle will follow?
Suppose v is the speed of the particle along the curve, then in traversing ds portion of the curve time spent would be \(\frac{{ds}}{v}\) so that total time taken by the particle in moving from highest point 1 to lowest point 2 will be
\[{t_{12}} = \int\limits_1^2 {\frac{{ds}}{v}} \]
Suppose vertical distance of fall upto point 2 be x, then from the principle of conservation of energy of the particle we find that
\(\begin{array}{l}\frac{1}{2}m{v^2} = mgx\\or\\v = \sqrt {2gx} \\then\\{t_{12}} = \int\limits_1^2 {\frac{{\sqrt {d{x^2} + d{y^2}} }}{{\sqrt {2gx} }}} dx\\{\rm{      = }}\int\limits_1^2 {\frac{{\sqrt {1 + {{\dot y}^2}} }}{{\sqrt {2gx} }}} dx\\{\rm{      = }}\int\limits_1^2 {fdx} \end{array}\)
\( f=\left ( \frac{1+\dot{y}^{2}}{2gx} \right )^{\frac{1}{2}} \)
For \({t_{12}}\) to be minimum equation
\(\frac{d}{{dx}}\left( {\frac{{\partial f}}{{\partial \dot y}}} \right) - \frac{{\partial f}}{{\partial y}} = 0\)
must be satisfied. From expression for \(f\) we find that
\(\begin{array}{l}\frac{{\partial f}}{{\partial y}} = 0\\\frac{{\partial f}}{{\partial \dot y}} = \frac{{\dot y}}{{\sqrt {2gx} \sqrt {1 + {{\dot y}^2}} }}\\\frac{d}{{dx}}\left( {\frac{{\dot y}}{{\sqrt {2gx} \sqrt {1 + {{\dot y}^2}} }}} \right) = 0\\or\\\frac{{{{\dot y}^2}}}{{2gx(1 + {{\dot y}^2})}} = c'\end{array}\)
Where c’ is the constant of integration.
Since c’ is a constant we can also write
\(\frac{{{{\dot y}^2}}}{{x(1 + {{\dot y}^2})}} = c\)
where c is also a constant. On integrating above equation we find
\(\begin{array}{l}\frac{{{{\dot y}^2}}}{c} = x(1 + {{\dot y}^2})\\or,\\{{\dot y}^2}\left( {\frac{1}{c} - x} \right) = x\\{{\dot y}^2}\left( {\frac{x}{c} - {x^2}} \right) = {x^2}\\\dot y = \frac{x}{{\sqrt {\frac{x}{c} - {x^2}} }}\end{array}\)
Putting \(\frac{1}{c} = 2a\) , and on integration we get
\(\int dy=\int \frac{x}{\sqrt{2ax-x^{2}}}dx\)
\( y=acos^{-1}(1-\frac{x}{a})-(2ax-x^{2})^{1/2}+c''\)

where c'' is new constant of integration.
In case c'' is zero then y will be zero for x=0.
As such the equation
\( y=acos^{-1}(1-\frac{x}{a})-(2ax-x^{2})^{1/2}\)

And this y represents an inverted cycloid with its base along y axis and cusp at the origin and is the curve that particle will follow.

Double pendulum

In case of a double pendulum find the expression for the kinetic energy of the system
We take a simple case where lengths and masses are same.see below in the figure

Here on being displaced the co-ordinates of two pendulums are
\(\begin{array}{l}{x_1} = l\sin {\theta _1}\\{y_1} = l\cos {\theta _1}\end{array}\)
For the first pendulum where \({\theta _1}\) is the angle through which the first pendulum have been displaced.
For second pendulum
\(\begin{array}{l}{x_2} = l\sin {\theta _1} + l\sin {\theta _2}\\{y_2} = l\cos {\theta _1} + l\cos {\theta _2}\end{array}\)
Where \({\theta _2}\) is the angle through which second pendulum has been displaced.
The total kinetic energy of the system is given by the expression
\(T = \frac{1}{2}m(\dot x_1^2 + \dot y_1^2) + \frac{1}{2}m(\dot x_2^2 + \dot y_2^2)\)


Which is the required result
Related Posts Plugin for WordPress, Blogger...